An Emission and Discard Priority Scheme for Optical Burst Switched Networks - Acquaah_PEK (Department of Electrical Engineering, 2024)
Optical burst switching (OBS) is a promising technology designed to meet the growing demands for internet handwidth and better Quality of Service (QoS). This technology provides all optical and high speed switching to overcome the bottleneck of electronic routers in the core network. In this thesis, I describe several critical issues that affect OBS networks. I highlight the need to resolve contention efficiently and cost-effectively to improve QoS in OBS networks. Techniques to resolve contention include wavelength conversion, deflection routing, optical buffering, and burst segmentation. Amongst these techniques, deflection routing is the most cost-effective because it requires no extra hardware and offers high throughput at low loads. However, deflection routing has shortcomings such as high burst loss at high loads and a high number of late packet arrivals, which hinder its performance. Hence, the aim of our study is to reduce the number of late packet arrivals due to burst deflections and to increase the efficiency of deflection routing. For this purpose, we propose an emission and discard priority (EDP) scheme. The EDP scheme assigns emission and discard priorities to bursts based on their QoS requirements. This type of burst differentiation allows routers to deflect bursts selectively and efficiently in the core network. Through simulations, I compare the performance of the deflection with EDP scheme, the no-deflection (drop policy) scheme. and the deflection scheme. I show that the deflection with EDP scheme has a higher throughput than the no-deflection scheme. and a higher throughput than the deflection scheme for loads L ~ 0.7 . Furthermore, I shm' that the deflection with EDP scheme has a lower proportion of late packet arrivals than the deflection scheme at all loads. As a result, the deflection with the EDP scheme outperforms the deflection scheme in terms of goodput for L ~ 0.7. Although the deflection scheme has higher goodput than the deflection with EDP scheme at low loads (L < 0.7), the iii deflection with EDP scheme performs fewer burst deflections, with a minimal loss in goodput. Hence, the deflection with EDP scheme has a higher goodput per deflection ratio, and is therefore more efficient than the deflection scheme without EDP.